Gereja Protestan di Timor Barat pada Masa Nederlandsch Zendeling Genootschap, 1820-1860 - Jacob, Fransico de Ch. A. (STFT Jakarta, Indonesia, 2021)
Abstract This article aims to describe and analyze - as comprehensively and objectively as possible - how the history of the Protestant Church in West Timor, especially during the Nederlandsch Zendeling Genootschap (1820-1860), took place. The results obtained clearly show that the Protestant Church continues to experience growth despite various challenges. One notable thing is that the growth of the Protestant Church in West Timor during the NZG period was not only due to the works of European missionaries but also because of the work of local people, both men, women, adults, and children. Keywords: Protestant Church, NZG, West Timor Abstract Artikel ini bertujuan untuk mendeskripsikan dan menganalisis – sekomprehensif dan seobjektif mungkin – bagaimana Sejarah Gereja Protestan di Timor Barat, khususnya pada masa Nederlandsch Zendeling Genootschap (1820-1860) berlangsung. Hasil yang didapat sangat jelas menunjukkan bahwa Gereja Protestan di Timor Barat pada masa NZG terus mengalami pertumbuhan, terlepas dari berbagai tantangan yang dihadapi. Satu hal yang penting dicatat adalah bahwa pertumbuhan Gereja Protestan di Timor Barat pada masa NZG tidak hanya disebabkan usaha para misionaris Eropa, melainkan juga karena pekerjaan orangorang lokal, baik laki-laki, perempuan, orang dewasa, maupun anak-anak. Kata-kata Kunci: Gereja Protestan, NZG, Timor Barat